Women's Empowerment Based on Entrepreneurial Skills in Adult Equality Education Program - Heryanto Susilo; I Ketut Atmaja Jhony Artha; Widodo Widodo; Monica Widyaswari; Desika Putri Mardiani (Communautaire: Journal of Community Service, 2025)
This community service aims to empower Package C students, particularly adult women at Anggrek Bulan Community Learning Center (CLC), Banyuwangi Regency, through entrepreneurship development training. The training focuses on business financial management, understanding market and business opportunities, and building business networks to support the development of agricultural businesses, specifically in cultivating golden dragon fruit. The implementation method involves several stages: first, socialization and discussion with the chairman of PKBM; second, identifying business development needs through the manager; third, training to enhance knowledge and skills in entrepreneurship; and fourth, mentoring, which is systematically conducted to assess the application of the training. The results of this initiative empower women by improving their entrepreneurial skills and addressing challenges they face in developing businesses. This training not only supports the personal growth of the participants but also strengthens local entrepreneurship, with a focus on agricultural business development. The research highlights the importance of continuous mentoring and skill enhancement for adults to overcome barriers to business success. Future recommendations suggest expanding similar programs to other regions to further empower marginalized communities and foster sustainable agricultural entrepreneurship.